Sofrimento na velhice: características da clientela de um serviço de psicologia no interior do Ceará - Sousa, Renata Vieira de (2024)
Faced with numerous adverse scenarios for the elderly concerning their health, family, social and work rearrangements, significant losses, among other nuances present in this phase of life, it is important to consider that such circumstances can trigger suffering for them. Given the accelerated increase in the elderly population in the country and the lack of initiatives focused on mental health in old age, it is increasingly necessary that there be research aimed at understanding them, in order to become aware of the most recurrent complaints among them and thus be able to guide and enable intervention actions according to their needs. The present study aimed to characterize the complaints of suffering of individuals aged 60 and older who were treated between 2013 and 2022 at the Applied Psychology Service (SPA) of the Federal University of Ceará (UFC), Sobral campus. It is, therefore, a documentary research, of a quantitative and descriptive nature, with investigation of the medical records of all users treated in this period and with this age group. To organize the data, perform percentage calculations for each information and produce tables, the digital tool Microsoft Excel 2010 was used. The results encompassed the sociodemographic characteristics and main complaints of suffering in this population, revealing the prevalence of elderly individuals with an average age of 67, female, without a partner, with more than two children, adherent to the Catholic religion, with low educational attainment, retired, residing in the municipality of Sobral with a family member, having some chronic condition, regularly using more than one medication, and having as main complaints depressive and anxious states and interpersonal conflicts. In conclusion, the complaints of suffering in this population are multifactorial, and attention to them should be provided in an integral manner. This and other studies can allow for a deeper understanding of the demands of this population in the municipality of Sobral - CE, as well as enabling the construction of public policies that address these needs, such as the creation of groups with themes related to the most recurrent complaints, enabling spaces for exchanging experiences, psychoeducation and strengthening bonds between participating members.